The Effect Of Storytelling Marketing On Purchasing Decisions Through Brand Equity As Intervening Variable On Gojek In Jakarta - Ridha Rizkia; Farah Oktafani (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2020)
As the capital city, Jakarta has become a city of traffic jams due to its dense and productive population. Private motorbike or motorcycle taxi is an alternative choice to deal with traffic jams. Gojek appears and becomes a solution for complaints against conventional motorcycle taxis. Many companies, including Gojek, are competing to do promotions to attract the attention of consumers. Gojek uses storytelling marketing strategies in creating advertisements and content in their social media. This research was conducted to determine the effect of storytelling marketing (X) on purchasing decisions (Y) through brand equity (Z) as an intervening variable. The analysis technique in this study uses quantitative methods with the type of exploratory research. Non-probability used as sampling method with the type of purposive sampling. The population size in this study was unknown and the sample used was 100 respondents. Based on descriptive analysis of storytelling marketing variables (X), brand equity (Z) and purchasing decisions (Y) are in the good category. While the results of the PLS analysis found that storytelling marketing influences purchasing decisions through brand equity as an intervening variable